2017
DOI: 10.1111/jfbc.12456
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and gastroprotective actions of butanol fraction ofZingiber officinaleagainst diclofenac sodium-induced gastric damage in rats

Abstract: This study was designed to investigate the antioxidant and antiulcer activities of flavonoid‐rich fractions of Zingiber officinale extract. The fractions, obtained by solvents of increasing polarities, were subjected to 2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging activity. The fraction which possessed the highest antioxidant activity was used to assess gastroprotective action against diclofenac sodium induced gastric ulcer in rats. Chromatographic profiling was carried out using LC‐ESI‐MS analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 73 publications
3
12
0
Order By: Relevance
“…This was in agreement with a previous study that showed that indomethacin-induced increases in mucosal MDA levels have been improved by classic anti-ulcer drugs like omeprazole [8]. Additionally, omeprazole significantly attenuated the increase of MDA, and protected the stomach from depletion of GSH in comparison to the ulcer control group [20]. The levels of SOD and CAT were significantly increased at the same time that levels of MDA were significantly decreased in pre-treated groups with omeprazole [113].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This was in agreement with a previous study that showed that indomethacin-induced increases in mucosal MDA levels have been improved by classic anti-ulcer drugs like omeprazole [8]. Additionally, omeprazole significantly attenuated the increase of MDA, and protected the stomach from depletion of GSH in comparison to the ulcer control group [20]. The levels of SOD and CAT were significantly increased at the same time that levels of MDA were significantly decreased in pre-treated groups with omeprazole [113].…”
Section: Discussionsupporting
confidence: 92%
“…This result is in harmony with that obtained in previous investigations [94]. Pretreatment with omeprazole prevented its reduction in the gastric mucosa in comparison to the ulcer control group [20]. Treatment with omeprazole, orally, can upregulate and increase the mucosal PG-E 2 level [116].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, rats with a gastric ulcer induced by diclofenac sodium were treated with the butanol extract of ginger. It could prevent an increase in the level of MDA and a decrease in catalase activity as well as the level of glutathione [34]. Moreover, the 6-gingerol-rich fraction from ginger could reduce the levels of H 2 O 2 and MDA, enhance antioxidant enzyme activity, and increase glutathione in rats with oxidative damage induced by chlorpyrifos [25].…”
Section: Bioactive Components and Bioactivities Of Gingermentioning
confidence: 99%